Creating Meaningful Museums: A Model for Museum Exhibition User Experience. Issue 1 (2nd January 2023) - King, Ellie; Smith, M. Paul; Wilson, Paul F.; Stott, Janet; Williams, Mark A.
Abstract: Combining existing knowledge of museum exhibition visitor experience with concepts of User Experience (UX), a model for Museum Exhibition User Experience (MEUX) is presented. The model was developed from research interviews and surveys with UK museum professionals and presents the museum exhibition experience from both museum and visitor perspectives. Its use as an evaluation tool for visitor experience is explored at Oxford University Museum of Natural History (OUMNH). In comparing results with those from staff, a disconnect emerged between museum and visitor preferences on motivations for visiting and what outcomes emerge from visits. The incorporation of the theoretical MEUX model into museum practice enables holistic conceptualization of the visitor experience through the pragmatic and hedonic qualities of an exhibition. With the development of further evaluation tools, this framework and methodology accurately captures institutional and visitor preferences and can evaluate how the development decisions of museums influence and impact the visitor experience.